St. Vincent and the Grenadines : Request for Disbursement Under the Rapid Credit Facility. (IMF Staff Country Reports; Country Report, 2011)
The Executive Board of the IMF has approved a disbursement of an amount equivalent to SDR 2.075 million under the Rapid Credit Facility for St. Vincent and the Grenadines to help the country manage the economic impact of Hurricane Tomas. The Board's approval enables the immediate disbursement of the full amount. The late-October 2010 hurricane inflicted significant damage to agriculture, housing, and infrastructure. The initial assessment conducted by the government estimated the cost of damage at 5 percent of gross domestic product.